As marcas linguísticas na construção das representações discursivas de vítima em inquéritos policiais - Gomes da Silva Neto, João; Maria de Fátima Silva dos Santos (Revista da Associação Portuguesa de Linguística, 2016)
This paper aims at aspects of a study on the textual analysis of legal discourse, focusing on the discursive representation of the victim in police inquiry documents related to cases of investigation of violence against women. The study is part of the general theoretical framework of Text Linguistics (LT) and, more specifically, of Textual Discourses Analysis, drawn up by the linguist Jean-Michel Adam (2011a). The concept of discursive representation proposed by TDA is one of the most important categories related to the semantic configuration in this analytical approach.